GUIDELINES FOR ENHANCING PALI LANGUAGE TEACHING SKILLS IN BUDDHISM PROGRAM IN HIGHER EDUCATION INSTITUTIONS OF RAJABHAT UNIVERSITY GROUP - Jayapattana, Supakanjana; Buddhasarn, Ampon; Hongsa, Chatmatee; Pomsuwan, Prayoon; Laechalad, Sompon; Vanhakic, Puthai; Vichanati, Jularat; Monle, Ekachai (Academic Journal Phranakhon Rajabhat University, 2023)
The purposes of this research were: 1) to study the problematic state of Pali language teaching in Buddhism program, 2) to analyze the guidelines for Pali language teaching in Buddhism program to align with the curriculum context, and 3) to propose the guidelines for enhancing Pali language teaching skills in Buddhism program. The research utilized a mixed research model, incorporating both a survey questionnaire and in-depth interviews through brainstorming group discussions. The statistics used for data analysis consisted of frequency, percentage, mean and standard deviation. The research results showed that: 1) the problematic state of Pali language teaching in Buddhism program consisted of 4 following aspects: the total mean of learning media at the highest level (4.07), followed by the total mean of teaching and learning (3.84), the total average of teaching activities (3.74), and the total average of curriculum (3.71), respectively. 2) The analysis of guidelines for Pali language teaching in Buddhism program to align with the curriculum context revealed that (1) the technique of knowledge transmission in Pali language was not in accordance with students’ nature. Buddha’s style should be applied. (2) The students lacked motivation in learning Pali, so the teacher should provide rewards. (3) No up-to-date teaching materials were found, so various digital media should be brought to the classroom, and (4) there were some problems regarding the curriculum, so the courses should be the same in every educational institution. 3) The new form of knowledge on suitable guidelines for enhancing Pali language teaching skills in Buddhism program was CLIA MODEL, where C = Curriculum, Pali language curriculum at the higher education level, L = Learning Outcome. Excellent Pali language I = Instructional Media A = Activity Pali language learning activities.